Asset Management Through Village Owned Enterprises (Case Study of Dayeuhuhur Village, Ganeas District, Sumedang Regency) - Fikri Rizal Fadhilah (GoResearch - Research & Publishing House, 2022)
This research is motivated by the problems that have arisen in Dayeuhluhur Village, Ganeas District, Sumedang Regency, namely the stagnant economic development in the region. Seeing these problems the Dayeuhluhur Village Government created BUMDes to manage existing assets and develop the village's economic potential. However, until now, as time goes by, BUMDes of Dayeuhluhur Village still have not received maximum results. Based on the results of the researchers' observations, there is still not optimal asset management by BUMDes Dayeuhluhur due to several obstacles, such as empowering the community, lack of human resources, and the small number of business fields being carried out. With the problems and obstacles that have been seen, researchers conducted research that aims to be material for evaluating and increasing the role of BUMDes in managing village assets. This research is a research with qualitative methods and descriptive analysis. This study measures the implementation dimensions, influencing factors, and the results of existing activities in implementing the role of BUMDes in managing village assets. The research results show not yet optimal in several dimensions such as activity plans, management performance, and community participation.